Mobility management in multicast environment - Sanni, Mistura L.; Hassan Abdalla Hashim, Aisha; Naji, Ahmed Wathik; Mahmoud Ahmed, Gharib Subhi (IIUM Press, 2011)
The communication in traditional network is unicast enabled by IP unicast protocol, on the contrary, group communication is the norm in human setting [1] and numerous applications abound like Mobile TV, Multimedia and General Content Distribution and other collaborative applications [2]. However, point-to-point communication in such use cases of lecture delivery will waste bandwidth, and broadcast is not even a good option as recipients should only be registered students and not all students. The only possible alternative is to employ multicasting.